ABOUT MODERN RESEARCH IN THE FIELD OF COMPLEX SULFIDE COMPOUNDS (STATE AND TRENDS) - M.A. Daurenbek,; A.K. Mazhibaev,; A.A. Bakibaev, (Academic Scientific Journal of Chemistry, 2020)
The article provides an overview of the most significant scientific papers (from more than 600 literature sources), devoted to the studies of complex sulfides, some of which are given in this research. There are examples of research in the field of the most promising complex sulfides CdZnS, AgInS, CuInS, ZnInS and the predicted scope of their practical application in the article. The tendencies in the research for physicochemical properties of complex metal sulphides are revealed